METHODS FOR STIMULATING THE CREATIVE SEARCH (Innovation in Woodworking Industry and Engineering design, 2026)
The design methods that stimulate students’ creative process and contribute to the rapid generation of ideas have been studied in this article.The aim of this report is to demonstrate the effectiveness of the methods and their application in the team student tasks.The applied methods stimulate the creative thinking by eliminating the mental blocks. These methods are characterized by the prominent role of the visual thinking in the construction of associations. This makes them extremely important for the design process, since the designer should be able to visualize his ideas.